Duodenal ulcer promoting gene (DupA), plasticity region genes and sigma factors in H. pyloristrains from Nigeria - Tolulope Funbi Jolaiya; Muinah Adenike Fowora; Charles Onyekwere; Rose Ugiagbe; Ifeanyi Ifeoma Agbo; Olufunmilayo Lesi; Dennis Amojuayi Ndububa; Olusegun Adekanle; Henry Akum Njom; Ayodeji Idowu; Isaac Adeyemi Adeleye; Moses Bamidele; et al. (Journal of Infection in Developing Countries)
Introduction: Helicobacter pylori is a principal cause of gastric cancer. The aim of this study was to determine the prevalence and contribution of duodenal ulcer promoting gene A (dupA), the plasticity region genes and sigma factors in relation to their pathological expression of H. pylori infections in the Nigerian population.